The Body Objectification and Social Capital Among Unesa Female Students: An Ecofeminist-Pierre Bourdieu Analysis - Eka Ningtyas; Ahmad Ridwan; Diyah Utami (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study examines the phenomenon of physical objectification and the use of beauty as a social asset among female students at Surabaya State University (Unesa) from an ecofeminist perspective and that of Pierre Bourdieu. On campus, women’s appearance often becomes the center of social attention, whether through comments on physical appearance, visual criteria set by organizations, or body representations on social media platforms. Given these conditions, this study aims to explain how beauty norms on campus are formed, how female students internalize these norms, and how beauty functions as a social asset in student relationships. This study employs a qualitative method, conducting in-depth interviews and participant observation with female students engaged in academic and organizational activities. Data were analyzed using ecofeminism theory to understand the domination and control over women’s bodies, as well as Bourdieu’s concepts of social capital, cultural capital, and habitus to explain how beauty operates as a strategic asset in social relations. Findings indicate that the objectification of the body manifests in visual judgments, beauty standards, and selection based on appearance. Beauty functions as cultural capital embodied in the body, which is converted into social capital within campus dynamics and provides broader opportunities to access social networks. These results emphasize that women’s bodies on campus are not merely private spaces but also a field of negotiation between individual freedom and campus aesthetic pressures. This study recommends that future research investigate the relationship between gender, campus media, and the construction of beauty in a digital context.